Neutronics analysis of spin-polarized fuel in spherical tokamaks - Jin Whan Bae; Katarzyna Borowiec; Vittorio Badalassi; Jason Parisi; Ahmed Diallo; Jon Menard; Andrei Khodak; Thomas Brown (Nuclear Fusion, 2025)
The effect of spin-polarized deuterium–tritium fuel on the blanket, magnets, and surrounding structures is analyzed for a spherical tokamak fusion power plant. The focus of this paper is the neutron flux distribution in the fusion device and the corresponding engineering considerations, such as tritium breeding ratio (TBR) and magnet fluence. Significant benefits were found for anti-aligned polarization: a 2.7% increase in the total TBR (which could increase significantly with further optimization) and an approximately 68% increase in the magnet lifetime. If the inboard breeding blanket can be replaced with extra shielding and magnets, then it could significantly increase fusion power with no loss of magnet lifetime. This would be accomplished by increasing the toroidal field strength.